Applicability of an abbreviated version of the oral impacts on daily performances (OIDP) scale for use among Tanzanian students - Masalu JR, A° (Blackwell Synergy, 2003)
The objective was to examine the applicability of an abbreviated version of the oral impact of daily performances (OIDP) inventory to Tanzanian adults attending the University of Dar es Salaam.